Sleep, Cognition and Cortisol in Addison’s Disease: A Mechanistic Relationship - Henry, Michelle; Thomas, Kevin Garth Flusk; Ross, Ian Louis (Frontiers in Endocrinology, 2021)
Sleep is a critical biological process, essential for cognitive well-being. Neuroscientific literature suggests there are mechanistic relations between sleep disruption and memory deficits, and that varying concentrations of cortisol may play an important role in mediating those relations. Patients with Addison’s disease (AD) experience consistent and predictable periods of sub- and supra-physiological cortisol concentrations due to lifelong glucocorticoid replacement therapy, and they frequently report disrupted sleep and impaired memory. These disruptions and impairments may be related to the failure of replacement regimens to restore a normal circadian rhythm of cortisol secretion. Available data provide support for existing theoretical frameworks which postulate that in AD and other neuroendocrine, neurological, or psychiatric disorders, disrupted sleep is an important biological mechanism that underlies, at least partially, the memory impairments that patients frequently report experiencing. Given the literature linking sleep disruption and cognitive impairment in AD, future initiatives should aim to improve patients’ cognitive performance (and, indeed, their overall quality of life) by prioritizing and optimizing sleep. This review summarizes the literature on sleep and cognition in AD, and the role that cortisol concentrations play in the relationship between the two.